The relationship between healthy eating obsessions, clinical eating disorder, and health anxiety: the dark side of the pursuit of healthy eating - Sanlier, Nevin; Ejder, Zeynep Bengisu; Kaya, Elif Yildiz (Frontiers in Psychology, 2025)
BackgroundThe obsession with healthy eating, as well as clinical eating disorders and health anxiety, is becoming increasingly common worldwide. Health anxiety, characterised by undue relevance about one’s health and reinforced by perfectionism, is a significant problem requiring intervention in individuals with orthorexia nervosa (ON) and other eating disorders.ObjectiveThis study was conducted to examine the relationship between orthorexia nervosa, eating disorder and health anxiety in adults.MethodsA total of 654 people (M = 211, F = 443) aged 19–50 answered sociodemographic questions and three instruments: the Orthorexia Nervosa Scale (ORTO-R), Clinical Impairment Assessment (CIA) and Short Health Anxiety Inventory (SHAI-18).ResultsSignificant positive correlations were observed between ORTO-R and CIA (r = 0.461), ORTO-R and SHAI-18 (r = 0.364), and CIA and SHAI-18 (r = 0.429) (all p = 0.000). Regression analyses showed reciprocal associations: higher CIA and SHAI-18 scores were related to higher ORTO-R scores (β = 0.350 and β = 0.203, respectively; Adjusted R2 = 0.266), and higher ORTO-R and SHAI-18 scores were related to higher CIA scores (β = 0.316 and β = 0.262, respectively; Adjusted R2 = 0.338). Similarly, both ORTO-R and CIA predicted SHAI-18 (β = 0.213 and β = 0.305, respectively; Adjusted R2 = 0.228).ConclusionIn conclusion, it was shown that ON, clinical eating disorder, and health anxiety were significantly related to each other. This finding may contribute to the development of public health communication strategies that promote balanced and evidence-based health behaviors.